Influence of the surface band structure on electron emission spectra from metal surfaces - Archubi, Claudio Darío (2014)
Electron distributions produced by grazing impact of fast protons on Mg(0001), Cu(111), Ag(111), and Au(111) surfaces are investigated, focusing on the effects of the electronic band structure. The process is described within the band-structure-based approximation, which is a perturbative method that includes an accurate representation of the electron-surface interaction, incorporating information of the electronic band structure of the solid. For all the studied surfaces, the presence of partially occupied surface electronic states produces noticeable structures in double-differential—energy- and angle-resolved—electron emission probabilities from the valence band. For Mg, Cu, and Ag these structures remain visible in electron emission spectra after adding contributions coming from core electrons, which might make possible their experimental detection, but for Au they are hidden by inner-shell emission.